Anti-Structuralist Structures: The Avant-Garde Struggles of French Fiction - Roland A. Champagne (Studies in 20th & 21st Century Literature, 1977)
A reassessment of French literary "structuralism" is timely in order to understand the development of avant-garde fiction. Piaget's parameters of wholeness, self-regulation, and transformation for a "structure" are useful critical tools in appreciating the relationships of avant-garde writers, texts, and readers to one another during the 1950's and 1960's in France. However, the writers and texts of that literary avant-garde refused to be congealed into a specific movement called "structuralism." Instead, they continually realized new forms to lead their readers away from the static artistic labels or "myths" which the representatives of French society consistently sought to impose. Those new forms revealed linguistic "structures" which linked writer, text, and reader such that we can now look beyond "structuralism" toward semiology and semiotics to understand the ideologies inherent within the linguistic components of writing and reading.
Keywords: avant-garde; French; structuralism